Apexification with Calcium Hydroxide: 27 Months Follow Up of a Case - Chowdhury, AFMA; Alam, A; Sarkar, UK; Mahmud, AA; Habiba, U; Rabby, MAI (Medicine Today, 2013)
Dental trauma is common in young patients with immature teeth. When necrosis of pulp follows in such a tooth, apexification of the root is the most recognized and accepted treatment of choice. Calcium hydroxide paste is the most popular material used to induce the apical hard tissue barrier which may be composed of different tissues. Hertwigs epithelial root sheath and (or) its remnants, the cell rests of Malassez may contribute to the apical closure. In the presented case, careful multidisciplinary treatment approach helped to regain esthetic and function. After 27 months the tooth showed every sign of success. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.16071 Medicine Today 2013 Vol.25(1): 42-45